The influence of anxiety and depression on the mental state of medical students during martial law - Ogorenko Вікторія; Shornikov Андрій (Psychosomatic Medicine and General Practice, 2023)
Actuality. Long-term exposure to stressors associated with martial law hurts the mental state of the country’s population. One of the risk groups is education seekers, for whom it is possible to sum up the stressful impact of education and other zonal factors. Earlier, in the example of countries in Africa, the Middle East and Kosovo, it was proven that the symptoms of anxiety and depressive disorders increased during military conflicts, particularly among medical students. The work aimed to study the symptoms of anxiety and depression in students of higher medical education at the Dnipro State Medical University and to determine their impact on the mental component of quality of life. Materials and methods: a four-fold one-moment cross-sectional survey questionnaire was conducted on the Google Forms platform. We interviewed 193 medical students of the Dnipro State Medical University. Data were collected after one, three, ten months and one year from the beginning of martial law. The level of anxiety was assessed using the generalized anxiety disorder scale (GAD-7), depression was assessed using the Patient Health Questionnaire (PHQ-9), and the mental component of quality of life was assessed using a self-administered questionnaire based on the VAS. Results. The median level of anxiety symptoms according to GAD-7 at the first stage of the study was 8 [5; 14] points with further reduction in the fourth stage to 5.5 [3.5; 7.5] points. The median level of depressive symptoms determined by PHQ-9 varies from 11 [6; 14] points after 1 month to 7.5 [4; 10] points 1 year after the start of martial law. Subjective assessment of working capacity in the subjects was 4 [3; 7] points for VAS with dynamics from 6 [4; 8] after 1 month of martial law, to 4.5 [4; 6] points after 1 year. According to the results of the correlation analysis, a relationship between indicators of anxiety, depression and the mental component of the quality of life was revealed. The correlation between anxiety and depression persisted as the duration of martial law increased, as did the relationship between anxiety and the mental component of quality of life at 1, 3, and 10 months of martial law. But after 12 months of martial law, anxiety ceases to affect the quality of life of the surveyed education seekers. Conclusions. Univariate and multiple logistic analyses were used to explore the psychometric characteristics that correlated with achieving a sufficient level of the mental component of quality of life. The combination of GAD-7 ≥ 10 and PHQ-9 ≥ 10 had the best predictive ability among the constructed models, for which the AUC was 0.777 (95% CI 0.711 – 0.834). By incorporating the ability to work into the model, we enhance its predictive power, resulting in an AUC of 0.844 (95% CI 0.785 – 0.892), which signifies its exceptional predictive capabilities. Thus, the presence of anxiety for GAD-7 more than 10 points increases the chances of not achieving quality of life by 2.885 (95% CI 1.167 – 7.133) times, the presence of depression for PHQ-9 more than 10 points – by 2.689 (95% CI 1.182 – 6.117) times, and subjectively reduced ability to work – 1.434 (95% CI 1.193 – 1.725) times.